Phenotypic and Molecular Characterization of Listeria Spp. from Raw Chicken Meat - Warke, Shubhangi R; Bobade , Sumedha S (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was aimed to find the prevalence of Listeria monocytogenes in raw chicken meat purchased across the Nagpur city. Cultural examination of 100 raw poultry meat samples revealed 35.0 % prevalence of Listeria spp. Among them, L. grayi was predominant (15 %) followed by L. monocytogenes (12 %), L. welshimeri (5 %), L. innocua (2 %) and L. seeligeri (1 %). A typical β-haemolysis clear zone was exhibited by 18 listeriae isolates. Of these, 12 isolates with characteristic biochemical pattern and showing haemolytic zone. All 12 L. monocytogenes isolates expressed the PI PLC activity. Multiplex PCR study of Listeria spp. revealed that four L. monocytogenes isolates were positive for plcA, actA, hlyA and iap genes. Amplified products of three virulence-associated genes namely, actA, hlyA and iap were detected in five L. monocytogenes and three L. monocytogenes isolates were positive for hlyA and iap genes. L. grayi isolates revealed the amplified product of iap gene. Two isolate of L. innocua were positive for actA and iap genes, Five L. welshimeri isolates and one L. seeligeri isolate were positive for iap gene, lacking plcA, actA and hlyA genes. As actA and iap genes were detected in a two isolate of L. innocua. It is clear that actA and iap genes are shared by L. monocytogenes and L. innocua. It is concluded that genes in three different combinations were recorded in Listeria spp. and that prfA and hlyA detected by PCR distinctively in L. monocytogenes suggest the usefulness of PCR amplification from various food samples.